The reasons for the loss of polyurea coatings adhesion to the concrete substrate in chemically aggressive water tanks. (December 2022) - Maj, Marek; Ubysz, Andrzej
Highlights: The driving power of osmosis under the polyurea coating. The relationship between the chemical resistance of a material and its flexibility. The relationship between the thickness of the polyurea coating and its tightness. Defects in polyurea applications. The reasons for the loss of polyurea coatings adhesion to the concrete. Abstract: The article discusses the use of one of coatings protecting and strengthening concrete surfaces. It is polyurea coatings to strengthen waterproofing in tanks for water and other related liquids. Details of polyurea application technologies for specific tank structures and preparatory works that must be performed before the application of spray polyurea coatings have been discussed, as well as essential points related to minor and major cracks, cover reprofiling, type of coating used in chemically aggressive environments, causes and examples of structures where destructive corrosion processes of concrete surfaces and, consequently, the polyurea coatings covering them have been activated. The presented examples of failures in the application of polyurea coatings arise due to insufficient knowledge about the coatings themselves and the substrate on which the coatings are applied, but above all in failing to follow the strict procedure for their application.